Upaya Pencegahan Kepolisian Terhadap Tindak Pidana Penganiayaan Oleh Anak Sekolah - Holpin Harun; Moh. R. U. Puluhulawa; Nuvazria Achir (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study aims to determine the police's efforts to prevent criminal acts of abuse by school children in Gorontalo. The type of research used is empirical law with a qualitative approach which will be analyzed descriptively. The results of this study indicate that the role of the police in preventing criminal acts of maltreatment by students is by pre-emptive efforts by conducting counseling and outreach. Furthermore, preventive efforts are carried out by way of patrols and evaluating the performance of the police. Meanwhile, repressive efforts are carried out by fostering and applying the principles of Restorative Justice. As for the efforts of the school, namely preventive efforts are activities carried out to prevent violations committed by students, curative efforts are efforts to anticipate violations committed by students, and coaching efforts are efforts to foster students who commit violations and have received punishments or sanctions that have been given by the school.